Aerodigestive clinic reduces emergency department and primary care utilization and increases access to ancillary and specialty care. (March 2022) - Volner, Keith; Montgomery, Agnes S.; Gould, Christine; Lustik, Michael; Liming, Bryan
Abstract: Objective: The study aimed to evaluate the effect of the aerodigestive clinic (ADC) on healthcare utilization. Study design: Retrospective quality improvement project; before and after. Setting: The ADC at Tripler Army Medical Center (TAMC) in Honolulu, HI. Methods: We retrospectively analyzed the electronic medical records of children ≤17 years old seen in the ADC at TAMC between April 2015 and June 2019. The number of emergency department (ED), primary care (PC), specialty care (SC), ancillary care (AC), and teleconsult (TC) encounters were tallied before and after one year of the initial intake visit. Results: A total of 261 children were included during the study period. Comparing visits before aerodigestive evaluation to after aerodigestive evaluation, the total number of visits before and after were similar with significant changes in the distribution of encounters. The total number of ED (−38%) and PC (−40%) visits decreased significantly (p < 0.001 for both). The total number of other visits were found to have non-significant increases. PC visits accounted for nearly one-third (31%) of all visits prior to the initial ADC visit, but only 19% of visits after. PC visits decreased for all age groups. ED visits decreased by nearly half (−48.1%) for ages 1–17, but there was no change for <1-year olds. Conclusion: There is a statistically significant reduction in the number of emergency department and primary care visits for patients seen in a multidisciplinary ADC. The distribution of visits differed strongly among age groups. These findings emphasize the positive impact that the multidisciplinary clinic has on healthcare utilization for pediatric aerodigestive patients.